on a new norm and the refinement of some inequalities between operator norm and the numerical radius - djaballah, souhaib (universty of elouedجامعة الوادي, 2021)
هدفنا الرئسي في هذه المذكرة هو تحسين بعض المتراجحات المهمة بين النظيم الاعتيادي للمؤثرات الخطية ونصف القطر الرقمي أو ايجاد متراجحات جديدة، ولهذا الغرض عرفنا نظيما جديدا على جبر المؤثرات الخطية المحدودة على فضاء هلبرتي مركب، درسنا خواص هذا النظيم وتطبيقاته على المترجحات بين النظيم الاعتيادي للمؤثرات الخطية ونصف القطر الرقمي، وفي الاخير تحصلنا على بعض النتائج. Our main target in this thesis is to refine some important inequalities between the usual operator norm and the numerical radius or obtain new inequalities. For that reason, we define a new norm on the algebra of all bounded linear operators on a complex Hilbert space. We study some properties of this norm, also we see its applications on the inequalities between the usual operator norm and the numerical radius. Finally we get some results.
mémoier master mathématique
Keywords: فضاء هلبرتي مركب، مؤثر خطي محدود، طيف مؤثر خطي، الصورة الرقمية لمؤثر خطي، نظيم المؤثرات الخطية الاعتيادي، نصف القطر الطيفي، نصف القطر الرقمي.; Complex Hilbert space, bounded linear operators, spectrum, numerical range, usual operator norm, spectral radius, numerical radius.